(untitled) (International journal of medical sciences, 2026)
Liver fibrosis is defined by progressive accumulation of extracellular matrix components in the liver, leading to scar tissue formation as a consequence of chronic hepatic injury. The condition most commonly develops in the setting of chronic hepatitis, where ongoing inflammation and hepatocyte damage drive fibrotic remodeling. Other contributing factors include hereditary metabolic disorders, portal hypertension, systemic diseases, and prolonged use of certain drugs.